METODE ROLE PLAYING TERHADAP PENCAPAIAN HASIL BELAJAR ANAK PAUD DARUSSALAM TAHUN PELAJARAN 2019-2020 - Resiana Resiana (Jurnal Salome : Multidisipliner Keilmuan, 2023)
ABSTRACT The problem in this study is the role playing method to achieve children's learning outcomes. This type of research is quantitative. The population in this study amounted to 20 people and the sample amounted to 10 people. Data collection tools using tests, direct observation and documentation. The test results were tested by testing the normality and homogeneity test as a prerequisite test for one sample t-test because and homogeneity so that the findings in the field with the non-parametric mean difference test and Mann Whitney. The results of this study can be concluded as follows: 1) How high is the achievement of learning outcomes of experimental class children in PAUD Darussalam has a mean of 29.30 with 9 indicators. 2) How high is the achievement of learning outcomes for control class children in PAUD Darussalam has a mean of 18.00 with 9 indicators. 3) There is a significant effect of using the Role Playing method on the achievement of children's learning outcomes in PAUD Darussalam, Z = -3,770 and Asymp. Sig. (2-tailed) = 0.00 <0.05 means that Ha: accepted and Ho: rejected, so it can be concluded that there is a significant difference between the experimental class and the control class. The experimental class was higher (mean) than the control class, namely the experimental class 15.40 and the control class 5.60, so the difference in the distance between the two was 9.8 considered as the effect of using the role playing method on learning outcomes of class A children.